An initial comparative study on the antennal morphology of Zoraptera (Insecta) with special reference to the sensilla - Faucheux, Michel J; Pačková, Gabriela; Kočárek, Petr; Kundrata, Robin (Scientific reports, 2025)
Zoraptera represent one of the smallest and least-known insect orders. They live mainly in tropical and subtropical forests and have a cryptic lifestyle. To obtain a better understanding of the detailed antennal morphology and its potential use for taxonomic research in this group, for the first time we conducted a scanning electron microscopy study of the antennal sensilla of Zoraptera. We examined two species of Spiralizoros (Spiralizoridae) and a single species of Spermozoros (Zorotypidae). We identified 10 different sensilla structures belonging to five main types in Zoraptera. While Böhm sensilla, sensilla campaniformia, sensilla chaetica (subtypes C1-C2), sensilla trichodea, and sensilla basiconica (subtypes B1-B2) were present in all species, sensilla chaetica C3, sensilla basiconica B3 and sensilla styloconica were present only in Spermozoros. We discussed the possible functions of all observed sensilla based on their external morphology. Additionally, we preliminarily compared the variability of antennal sensilla between the families as well as two species of the same genus, and investigated the differences between both sexes as well as apterons and dealates of the same species. This study provides the first step toward future research on antennal morphology within Zoraptera and its significance for their systematics.
Keywords: tykadla členovců; Spermozoros; Animals; mužské pohlaví; hmyz; Sensilla; ženské pohlaví; Microscopy, Electron, Scanning; Insecta; zvířata; Scanning electron microscopy; Female; sensilla; Arthropod Antennae; Polyneoptera; Spiralizoros; Male; mikroskopie elektronová rastrovací